The Real estate job finder. (Englewood Cliffs, New Jersey : Prentice-Hall, 1981)
This book is a part of a series. The series begins with a book entitled How to Find Your Life's Work: Staying Out of Traps and Taking Control of Your Career, which provides an overview and offers basic tools which enhance the use of the other books. The other books are career guides to various industries and professions; this one is about the real estate industry. The purpose of the series is to provide information on industries to jobseekers at every level, and to other people concerned with careers, such as guidance counselors, employment agents, recruiters, and so on. The guides present a general view of each industry as well as detailed information that will help job hunters find exactly what they need to pursue a particular job in a particular industry. Because of the information they contain, the guides also stand on their own as valuable texts for advertising, marketing, sales, promotion, and management personnel in the industries discussed. They show how each industry works and where the best information on it can be quickly located.
1. An Overview of Real Estate -- 2. The Real Estate Professional: Two Interviews -- 3. Reframing your Approach to Job Search -- 4. Your Real Estate Information Center.
Includes bibliographical references and index.
Keywords: REAL ESTATE AGENTS